Einführung in die grammatische Beschreibung des Deutschen. Zweite, überarbeitete Auflage - Schäfer, Roland (Textbooks in Language Sciences, 2016)
"This textbook is an introduction to the descriptive grammar of German on the levels of phonetics, phonology, morphology, syntax, and graphemics. It is a recommended read for anyone interested in the grammar of German and especially for students of German philology. The book focuses on how grammatical generalizations are derived from concrete linguistic material while covering a huge number of the important phenomena of German grammar. No specific theoretical framework is adopted in the book but it constitutes an ideal starting point for reading more theory-specific textbooks and accessible research papers. Despite its length, the book is suitable for inclusion in all sorts of curricula, mostly because the five parts of the book can be read separately. Almost all chapters contain a large number of exercises, many of which come with solutions in the appendix. The second edition was prepared based to a large extent on reader feedback. It introduces numerous corrections and improvements. Most prominently, the chapter on phonology was completely rewritten so as to provide a better description of the relevant generalizations of German syllable structure."